PENGARUH FASHION INVOLVEMENT, SHOPPING LIFESTYLE, HEDONIC SHOPPING VALUE DAN POSITIVE EMOTION TERHADAP IMPULSE BUYING PRODUK FASHION PADA PELANGGAN DUTA MALL BANJARMASIN - Irma Sucidha (Islamic University of Kalimantan MAB Banjarmasin, 2019)
This research is intended to find out and analys the effect between fashion involvement (X1), shopping lifestyle (X2), hedonic shopping value (X3) and positive emotion (X4) as exogenous variable towards impulse buying (Y1) as endogenous variable to the Duta Mall Banjarmasin customer. This study used the quantitative research by spreading questioners to the customer of Duta Mall Banjarmasin who shop about 145 persons. The sample was taken by the purposive sampling method. The measurement of variable used the bipolar adjective scale with the weight scale from 1 to 10. To find out the effect of X variable towards Y variable used Structural Equation Modelling (SEM). The result concluded that (1) there is a negative influence and insignificant variables of fashion involvement (X1) towards impulse buying (Y) in the amount of -7,4%. (2) shopping lifestyle variable (X2) influence significantly and positive in the amount 72,9% towards impulse buying (Y), hedonic shopping value variable (X3) influence significantly and positive in the amount 17,2% towards impulse buying (Y) and (4) positive emotion variable (X4) influence significantly and positive in the amount 17,8% towards impulse buying (Y). Keywords: Fashion involvement, shopping lifestyle, hedonic shopping value, positive emotion, impulse buying.